Transformative Professional Development in Unlikely Places: Twitter as a Virtual Learning Community - Kathleen P. King (Adult Education Research Conference, 2011)
This case study reveals new dimensions of transformative learning occurring through informal learning opportunities. The research results demonstrate that the individual’s learning spans understanding, networking, professional identity development, and transformative learning. Specifically, virtual online communities facilitated through social media provide professional networks and social relationships beyond the scope of the individual’s usual interactions and experience. Discussion and recommendations include using social media and virtual communities as instructional strategies for graduate studies and continued learning beyond formal education. The educational significance includes facilitating transformative learning in informal learning contexts, and using social media and online communities for professional learning.
Keywords: transformative learning; social media; informal learning; professional development